Parametric resonance of submerged floating pipelines with bi-frequency parametric and vortex-induced oscillations excitations. (3rd April 2017) - Yang, Hezhen; Wang, Zhiqian; Xiao, Fei
ABSTRACT: This study investigates the parametric resonance of submerged floating pipelines during vortex-induced excitations. The submerged floating pipeline is considered as a potential solution for deep-water fluid transportation. However, the parametric resonance due to vortex-induced oscillations must be a major concern for its design, because it can lead to the huge motion and fatigue damage of the pipeline. Thus it is essential to predict the parametric resonance of the submerged floating pipeline system. Bi-frequency Hill's equations of the dynamic responses of the pipeline are derived, and vortex-induced forces are main causes of parametric excitations. Hill stability diagrams are used to analyse stability of solutions of the equations. The differences between the parametric resonance and vortex-induced resonance are also compared. The results show that the parametric resonance may take place in rigid body motion and transverse vibration of the submerged floating pipeline. The pipeline will have large vibration in both cross-line and in-line directions at the same time when the parametric resonance occurs, which, however, cannot happen in just the vortex-induced resonance. Some effective measures are given to designers to avoid the parametric resonance for the submerged floating pipeline design.